Insights into the role of neutrophils in neuropsychiatric systemic lupus erythematosus: Current understanding and future directions - Sim, Tao Ming; Mak, Anselm; Tay, Sen Hee (Frontiers in Immunology, 2022)
Central nervous system (CNS) involvement of systemic lupus erythematosus (SLE), termed neuropsychiatric SLE (NPSLE), is a major and debilitating manifestation of the disease which can masquerade as common and non-specific features such as cognitive deficits, headache and mood disorders. Research to elucidate the complex pathogenesis of NPSLE has seen recent advancements in mechanistic understanding and we are just beginning to unravel the mysteries behind the immunologic basis of NPSLE. The pathogenic pathways implicated in NPSLE are multifarious and various immune effectors such as cell-mediated inflammation, autoantibodies and cytokines including type I interferons have been found to act in concert with disruption to the blood-brain barrier and other neurovascular interfaces. Far beyond antimicrobial functions, neutrophils are emerging as decision-shapers during innate and adaptive immune responses. Activated neutrophils have been recognized to play be involved ischemic and infective processes in the CNS by releasing neutrophil extracellular traps (NETs), matrix metalloproteinase-9 and proinflamatory cytokines. In the context of NPSLE, these mechanisms contribute to disruption of the blood-brain barrier, promote neuroinflammation and provide modified proteins externalized on NETs to serve as self-antigens. Neutrophils that sediment within the peripheral blood mononuclear cell fraction after density centrifugation of blood are generally defined as low-density neutrophils or low-density granulocytes. Low-density neutrophils are a proinflammatory subset of neutrophils that are increased with SLE disease activity and are primed to undergo NETosis and release cytokines such as interferon-α and tumor necrosis factor. This review discusses the immunopathogenesis of NPSLE with a focus on neutrophils as a core mediator of disease and spotlights the potential for translational research in NPSLE.